Research on the cable routing optimisation by hybrid intelligent water drop algorithm. (2018) - Li, Chunquan; Zhang, Ming; Shang, Yuling; Hu, Yuwei
Cable assembly problem is formulated as searching for cable routes and the cable routing problem is one of the most challenging optimisation problems. Cable routing is the process of searching for obstacle-free path, which is constrained by the assembly points. Before routing, the routing environment is simplified to a two-dimensional grid map for computing reduction. In order to get the optimisation routing path, a novel approach of hybrid intelligent water drop algorithm (HIWDA) for cable routing is proposed, which is the hybridisation of particle swarm optimisation (PSO) and intelligent water drop algorithm (IWDA) for global searching and local searching respectively. In addition, B-spline curves are employed for smoothing routes obtained by HIWDA and making it more practical and more feasible for assembly. The result of HIWDA is verified by comparison with other algorithms in simulation on experiments.